2004
DOI: 10.1037/0012-1649.40.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Early Social Attention Impairments in Autism: Social Orienting, Joint Attention, and Attention to Distress.

Abstract: This study investigated social attention impairments in autism (social orienting, joint attention, and attention to another's distress) and their relations to language ability. Three- to four-year-old children with autism spectrum disorder (ASD; n = 72), 3- to 4-year-old developmentally delayed children (n = 34), and 12- to 46-month-old typically developing children (n = 39), matched on mental age, were compared on measures of social orienting, joint attention, and attention to another's distress. Children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

51
849
2
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,175 publications
(919 citation statements)
references
References 50 publications
51
849
2
17
Order By: Relevance
“…However, in this study, a significant correlation was found between the IJA and RJA skills of children with ASD, which is in line with the results of some other studies in young children with ASD (e.g., Bono, Daley, and Sigman, 2004;Dawson et al, 2004;Siller andSigman, 2008, Toth, Munson, Meltzoff, Dawson, 2006). Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level).…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 92%
See 2 more Smart Citations
“…However, in this study, a significant correlation was found between the IJA and RJA skills of children with ASD, which is in line with the results of some other studies in young children with ASD (e.g., Bono, Daley, and Sigman, 2004;Dawson et al, 2004;Siller andSigman, 2008, Toth, Munson, Meltzoff, Dawson, 2006). Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level).…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 92%
“…The individual differences in RJA skills were significantly related to mental age and language abilities. However, as other studies have shown, children with ASD are more impaired in RJA skills than children with developmental delays or children matched on mental age (e.g., Dawson et al, 2004).…”
Section: Response To Joint Attention Skillsmentioning
confidence: 78%
See 1 more Smart Citation
“…This paradigm had been previously shown to elicit such empathic responses from typically developing infants (Zahn-Waxler, Robinson, & Emde, 1992; Zahn-Waxler & Radke-Yarrow, 1982) as well as children with autism and with intellectual disability (Dawson et al, 2004; Sigman, Kasari, Kwon, & Yirmiya, 1992). Such early-emerging behavioral responses to another person’s distress have been found to be developmentally linked with later expressions of empathy (Hutman & Dapretto, 2009; Zahn-Waxler, Radke-Yarrow, Wagner, & Chapman, 1992) and thus represent a good proximal domain for an initial exploration of the developmental consequences of attachment security in autism.…”
Section: Developmental Consequences Of Attachment Security In Autismmentioning
confidence: 99%
“…Such early-emerging behavioral responses to another person’s distress have been found to be developmentally linked with later expressions of empathy (Hutman & Dapretto, 2009; Zahn-Waxler, Radke-Yarrow, Wagner, & Chapman, 1992) and thus represent a good proximal domain for an initial exploration of the developmental consequences of attachment security in autism. A focus on empathy is further motivated by previous studies indicating that preschool-age children with autism (Dawson et al, 2004; Sigman et al, 1992) as well as infants and toddlers (Charman et al, 1997; Hutman et al, 2010) are less attuned to the displays of distress of others and are less likely to engage in comforting behaviors when compared to typically developing children.…”
Section: Developmental Consequences Of Attachment Security In Autismmentioning
confidence: 99%